1976
DOI: 10.1203/00006450-197608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Inulin Clearance in the Newborn Infant: Relationship to Gestational and Postnatal Age

Abstract: Thirty-eight healthy newborn infants with gestational ages ranging from 25 to 42 weeks were studied at 2 days to 9 weeks postnatal age to evaluate the rate of glomerular maturation after birth. Glomerular function was assessed by a constant infusion method for inulin clearance (Cin). Cin was nearly identical when measured by the traditional clearance method and by the constant infusion technique. The Cin of 22 infants 2-3 days old ranged from 0.6 to 17.9 ml/min and was directly related to gestational age (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 5 publications
(7 reference statements)
3
41
0
1
Order By: Relevance
“…PNA and GA are known predictors of glomerular filtration rate (GFR) maturation and drug Cl. 15,24,25 TEMP being an independent covariate is very interesting. It can be debated that PNA (reflecting GFR maturation and drug Cl) and TEMP are correlated and a distinction in the effect of both on Cl is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…PNA and GA are known predictors of glomerular filtration rate (GFR) maturation and drug Cl. 15,24,25 TEMP being an independent covariate is very interesting. It can be debated that PNA (reflecting GFR maturation and drug Cl) and TEMP are correlated and a distinction in the effect of both on Cl is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Three-quarters of ml of whole blood was obtained by heel puncture, 45 min after the onset of the inulin infusion for plasma inulin (13) and creatinine. To minimize the quantity of the total whole blood drawn from these infants, one sample was taken for inulin; it has been previously shown that low birthweight infants reach a serum steady-state for inulin 45 min after the onset of the infusion (13). Serum bilirubin was measured in 26 studies (14).…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…GFR values were determined by means of the continuous inulin infusion technique on the third day of life (5,6,12). Inulin was obtained from Laevosan Gesellschaft mbH (Lienz, Austria) and was administered as a solution containing 25 g inulin/L at an infusion rate of 0.6 mL/kg/h.…”
Section: Patientsmentioning
confidence: 99%